Screening, Brief Intervention, and Referral to Treatment to Prevent Post-Traumatic Stress Disorder After Gunshot Wounds. Issue 9 (September 2022) - Castater, Christine; Raney, Emma; Nguyen, Jonathan; Reed, Kendal K.; Thompson, Alexis N.; Greene, Wendy R.; Sola, Richard; Grant, April A.; Sciarretta, Jason D.; Todd, S. Rob; Williams, Keneeshia N.; Hurst, Stuart; et al.
Screening, brief intervention, and referral to treatment (SBIRT) is an intervention originally developed to prevent and deter substance abuse. Adaptation of the SBIRT model to prevent post-traumatic stress disorder (PTSD) may potentially reduce acute stress symptoms after traumatic injury. We conducted a prospective randomized control study of adult patients admitted for gunshot wounds. Patients were randomized to intervention (INT) vs. treatment as usual (TAU) groups. INT received the newly developed SBIRT Intervention for Trauma Patients (SITP)—a 15-minute session with elements of cognitive behavioral therapy techniques. SITP took place during the index hospitalization; both groups had followup at 30 and 90 days at which time a validated PTSD screening tool, PCL-5, was administered. Most of the 46 participants were young (mean age = 30.5y), male (91.3%), and black (86.9%). At three-month follow-up, SBIRT and TAU patients had similar physical healing scores but the SBIRT arm showed reductions in PTSD symptoms.